Femur Fracture in a Newborn During Emergency Cesarean Delivery: A Case Report - Yeshey Dorjey; Abhisek Pradhan; Gitanjali Lamichaney (Clinical Case Reports)
ABSTRACT Birth injury occurs when the delivery process is not appropriately attended, and the use of improper techniques or maneuvers while conducting the delivery. Cesarean delivery is considered safe as compared to vaginal for the breech presentation. However, this case reports a case of femur fracture of a newborn that occurred during an emergency cesarean section performed for breech presentation. This highlights cesarean section for malpresentation is not completely safe.